The Torah unabridged: the evolution of intermarriage law in the Hebrew Bible - Tooman, William A. (Critical studies in the Hebrew Bible, 2022)
The Torah Unabridged is a detailed examination of legal reasoning in the Hebrew Bible. Focusing on the exegetical operations by which biblical laws related to intermarriage were applied to circumstances and persons that lie outside the sphere of their explicit content, this book reconstructs the ways in which laws regarding intermarriage evolved, were interpreted, and were applied across time and place.William A. Tooman argues that the “exegetical impulse” to expand upon the gaps left by laws relating to marriage in the Torah is expressed in several distinctive ways in later texts in the Hebrew Bible. Adopting a diachronic approach, Tooman examines the techniques biblical writers used in their appropriation, expansion, and manipulation of legal ideas within earlier biblical texts in order to apply the laws to more situations, circumstances, and people. Tooman’s analysis reveals that from Exodus to Ezra-Nehemiah, legal reasoning on intermarriage moved in a singular direction: toward an ever-greater restriction of marriage between Israelites/Jews and gentiles. The final chapter sums up the ways that this was accomplished, summarizing the logical and exegetical operations executed in the process of expanding the relevance of these laws, and describing the hermeneutical assumptions that motivated the process.Grounded in a detailed philological analysis of the Hebrew texts, this tightly argued monograph is an important impetus to further debate in the field. It will be welcomed by biblical scholars and by specialists in the history of law